Representasi Pendidikan Karakter dalam Soal-Soal Ujian Nasional Bahasa Indonesia - Zainal Abidin (Balai Bahasa Sumatera Utara, 2021)
Character education has been promoted by the Ministry of National Education of Indonesia for a long time. Every party, especially, every school is called to implement and grow the character education amongst students. Learning activities have been driven to the establishment of the character. However, an evaluation on character education that were taught has never been carried out yet. Therefore, it is necessary to find out how national examination questions represent the character education. This study aimed to describe the character education in Indonesian language national examination. Data containing words, phrases and sentences were collected from Indonesian language national examination questions of 2019. The method used to collect the data was the qualitative method through observation and note-taking. The research findings revealed that there were 14 leadership characters found in the Indonesian language national examination questions of 2019. They were friendly/ communicative, caring for the environment, creative, curios, social care, hard work, nationalism, respect for achievement, democratic, loving homeland, peace